Dysfunctional telomeres in BRCA2 deficient breast cell lines - Alexander Örn Kárason 1998- (2023)
Breast cancer is the most frequently diagnosed cancer in women worldwide. It accounts for approximately 30% of all diagnosed cancers in Icelandic women. According to estimates, 5-10% of all breast cancer diagnoses are familial, that tends to be more frequent in younger women than sporadic cancers. 3-6% of breast cancer globally are caused by germline mutations in the tumor suppressor genes breast cancer gene 1 and breast cancer gene 2 (BRCA2). A BRCA2 999del5 founder mutation is present in 0.7% of the general population of Iceland and in 6-7% of breast cancer cases. BRCA2 plays an important role in homologous recombination (HR) DNA repair and protects stalled replication forks from degradation. BRCA2 also seems to have an important role in maintaining telomere stability. When HR is inactive due to BRCA2-deficiency, more error-prone repair pathways, such as polymerase theta-mediated end-joining (TMEJ) and single-strand annealing (SSA) controlled by polymerase theta (POLQ) and radiosensitve 52 (RAD52), respectively, may take over to maintain genomic integrity. The aim of the study was to analyse involvement of TMEJ and SSA backup pathways in telomere maintenance, as well as telomere instability, when BRCA2 is not fully expressed. Two breast epithelial cell lines, A176 (BRCA2-999del5-1N) and A240 (BRCA2-999del5-2N) with the BRCA2 999del5 germline mutation were treated with small interfering RNA (siRNA) to silence BRCA2, POLQ and RAD52 expression, independently. BRCA2, POLQ and RAD52 expression was silenced by siRNA, separately, in A176 and A240 cell lines. siRNA silencing was performed for 48 hours (hr) and 72 hr. BRCA2 silencing efficiency was more than 70% in both cell lines. On the other hand, POLQ and RAD52 silencing efficiency was only ranging from 14% to 50%. Cell proliferation was measured with IncuCyte ZOOM live cell imaging. Cell confluency was significantly decreased after siBRCA2 treatment in both cell lines after 48 hr treatment. However, siPOLQ and siRAD52 treatment in both cell lines showed low ...